Evaluating of sportۥs morals of the Students of Physical Education and sport. departments in the University of Mosul - Abdullah, Alaa (Journal of Physical Education, 2010)
The study aimed at evaluating of sportۥs morals of Physical Education and sport. department Students . It also aimed at identifying the scope in which the percentage of sportۥs morals increases, and the researcher hypothesized that there is a high level of sportۥs morals In addition, the level of sportۥs morals of the individuals of the sample under study varies according to the variability of the scopes. The researcher used the questionnaire as a means for collecting data. The sample of the study consisted of students of college and department of Physical Education-class(4). The researcher used the arithmetical mean, standard deviation, centesimal weight, simple correlative coefficient, and discrepancy analysis (T) as means for collecting data. The researcher found that there is a good level of sportۥs morals.